Are flection Of Accounting for Contingent Assets, Liabilities and Provision on Faithful Representation Characteristic of Accounting Information - التميمي عباس حميد; بيره ندى كاكي (Journal of Economics and Administrative Sciences, 2016)
Abstract This research aims to study the reflection of accounting for contingent assets and liabilities and provisions on Faithful Representation characteristic of accounting information, To achieve this goal has been questionnaire design has been distributed to research sample, which consists of (50) listed company on the Iraq Stock Exchange and from all different sectors. The research concluded that the measurement and disclosure of contingent assets, liabilities and provisions to achieve Faithful Representation characteristic of Accounting information and sub-characteristics relevant, as it ranged arithmetic mean of the results of testing president hypotheses and its subsidiaries between (19-20) is larger than the arithmetic mean premise of (15). The research recommended to the need for measurement and disclosure for contingent Assets and liabilities and provisions to different groups of users of financial information because of their impact on the credibility of that information, and thus influence the making economic decisions, Moreover need to Punish Companies Administrations That do not disclosure them for the Responsible Authorities.